The making of design : from the first model to the final product - Terstiege, Gerrit (Birkhauser, 2009)
From the Publisher: this book takes an in-depth look at design processes, with twenty-five depictions of "the making of" products from a wide variety of industries. Its primary focuses are furniture design, transportation design, and household appliances. Renowned designers like Konstantin Grcic, the Bouroullecs, Stefan Diez, Hella Jongerius, and Sir Norman Foster offer step by step accounts of how they go about designing products for Vitra, Grundig, Jura, and Authentics-the tools they use for visualization and how projects change during the model phase. Plus: an interview with design legend Dieter Rams on realized and unrealized products for Braun